Taking technologies to a greater scale - Sseguya, H.; Chikowo, Regis; Chimonyo, Vimbayi Grace Petrova; Chipungu, Felistus P.; Groot, Jeroen C.J.; Muthoni, Francis K.; Ngulu, F.; Thierfelder, Christian L. (CAB International, 2022)
This chapter presents a definition of 'scaling' and outlines the key elements for success based on the experiences gained from Africa RISING research and dissemination in East and Southern Africa (ESA). Three examples are presented: (a) research and development partnerships; (b) community based scaling through seed systems; and (c) outdoor advertising for orange-fleshed sweet potato. It presents experiences and lessons learned from using these approaches to transfer and scale the technologies.